Isolation and identification of the Newcastle disease virus from field outbreaks in broiler and layer flocks in Iraq: Mushtaq T. B. AL-Zuhariy1; Sahar Hamdi Abdulmaged1; Raed H. S. Rabee2 and Amer A. A. AL-Baldawi3 - AL-Zuhariy, Mushtaq T. B. (The Iraqi Journal of Veterinary Medicine, 2017)
Newcastle disease is one of serious pathological problems and causes of vast economic losses during 2011-2016 in Iraq. The disease caused high mortalities in all types of poultry nevertheless of vaccination. In this study all samples were collected from infected flocks with clinical signs of the disease. Inoculation of chicken embryonated eggs was carried out for virus isolation, identification, Haemagglutination and Haemagglutination Inhibition assay. Using Reverse Transcriptase-Polymerase Chain Reaction to confirm the presence of the virus, Intra Cerebral Pathogenicity Index and Mean Death Time were used to confirm all the isolates that were velogenic. The important determinant of Newcastle disease virus pathogenicity is fusion protein that has been used for phylogenetic analysis. sequencing and compared genetically of Newcastle disease virus Iraqi isolate to publish sequences acquired from GenBank showed 99% sequence similarity to the Iran isolate IRI 1392k (KJ176996.1). It can concluded from these data that introduction new virus was occurred in Iraq.